2014
DOI: 10.3390/nu6125434
|View full text |Cite
|
Sign up to set email alerts
|

The Omega-3 Fatty Acid Docosahexaenoic Acid Attenuates Organic Dust-Induced Airway Inflammation

Abstract: Workers exposed to organic dusts from concentrated animal feeding operations (CAFOs) are at risk for developing airway inflammatory diseases. Available preventative and therapeutic measures for alleviating dust-induced lung disease are inadequate. Because omega-3 fatty acids can mitigate inflammatory processes, we aimed to determine whether nutritional supplementation with the omega-3 fatty acid docosahexaenoic acid (DHA) could reduce the airway inflammatory consequences of exposures to organic dust. Aqueous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 58 publications
7
29
0
Order By: Relevance
“…Similar beneficial results have been observed in adult animals in acute lung injury models (8,11,20,47). Other pulmonary disease models where benefits were seen with DHA or its downstream metabolites include cystic fibrosis, asthma, and pulmonary fibrosis (29,31,51).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Similar beneficial results have been observed in adult animals in acute lung injury models (8,11,20,47). Other pulmonary disease models where benefits were seen with DHA or its downstream metabolites include cystic fibrosis, asthma, and pulmonary fibrosis (29,31,51).…”
supporting
confidence: 66%
“…Similar beneficial results have been observed in adult animals in acute lung injury models (8,11,20,47). Other pulmonary disease models where benefits were seen with DHA or its downstream metabolites include cystic fibrosis, asthma, and pulmonary fibrosis (29,31,51).In a recent issue of the journal, Ali and colleagues (1) elegantly show that apoptosis persists in the lungs of 8-wk-old mice who had been exposed to perinatal inflammation (maternal systemic inflammation) and postnatal hyperoxia [up to postnatal day (PND) 14] followed by return of the animals to room air. This was accompanied by upregulation of some of the proteins associated with the apoptotic pathways.…”
supporting
confidence: 64%
“…Interestingly, it has been reported that diets high in poly-unsaturated fatty acids may significantly decrease mortality risk while improving clinical outcomes in patients experiencing acute lung injury or acute respiratory distress syndrome (37). We have recently demonstrated that treatment with the omega-3 fatty acid docosahexaenoic acid for one week prior to a single DE exposure significantly reduced neutrophil influx and pro-inflammatory cytokine production (38). Yet, no previous studies have reported a role for SPM in organic dust-induced inflammation or identified the specific effects that MaR1 may influence during these lung inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, it is well known that the organic acids (esters) have various pharmacological activities, such as antiinflammatory activity . And total organic acids have also been reported to have the activities of antitussive effect in crude and processed Pinelliae Rhizoma.…”
Section: Resultsmentioning
confidence: 73%